2021
DOI: 10.1002/jmv.27298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on the incidence of dengue fever in Peru

Abstract: Dengue virus and severe acute respiratory syndrome coronavirus 2 coexist in dengueendemic countries; therefore, the adoption of preventive measures is essential to control the spread of both viruses. We conducted an ecological study to compare the temporal patterns of the incidence of dengue before and during the Coronavirus disease 2019 (COVID-19) pandemic in Peru. A time-series analysis comparing the incidence of dengue using a Student's t test with variance correction was performed. Poisson

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“… 3 The high burden of dengue and COVID‐19 infections increases the possibility of co‐infection, which is a significant health concern due to the overlapped symptomatology and similar laboratory findings of the two conditions in dengue‐endemic regions. 4 , 5 This overlap would make reaching the correct diagnosis and, subsequently, the proper management challenging for both diseases. 5 Furthermore, there are previous studies about the co‐infection of dengue and COVID‐19 during the current pandemic, with reported worse clinical manifestations and higher complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 The high burden of dengue and COVID‐19 infections increases the possibility of co‐infection, which is a significant health concern due to the overlapped symptomatology and similar laboratory findings of the two conditions in dengue‐endemic regions. 4 , 5 This overlap would make reaching the correct diagnosis and, subsequently, the proper management challenging for both diseases. 5 Furthermore, there are previous studies about the co‐infection of dengue and COVID‐19 during the current pandemic, with reported worse clinical manifestations and higher complications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, approximately more than 400 million cases are infected with dengue fever each year, transmitted by the Aedes aegypti mosquito 3 . The high burden of dengue and COVID‐19 infections increases the possibility of co‐infection, which is a significant health concern due to the overlapped symptomatology and similar laboratory findings of the two conditions in dengue‐endemic regions 4,5 . This overlap would make reaching the correct diagnosis and, subsequently, the proper management challenging for both diseases 5 .…”
Section: Introductionmentioning
confidence: 99%
“…and Plasencia et al. ( Lim et al., 2020 ; Plasencia-Dueñas et al., 2021 ) with data collection period of less than two years in non-exposed group(COVID-19 pre-pandemic) were selected for comparison with the article that had the same study site and analytic methods but a longer data collection period in non-exposed group. A subgroup meta-analysis revealed that the pooled RR value in the study with less than two years of observation in the control group was overestimated ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the COVID-19-related unprecedented situation, dengue would retain its epidemic status in most resource-constrained countries of Asia and Latin America. Indeed, control measures of dengue infection are neglected in many epidemic countries as excessive prioritization is given to preventing and control of SARS-CoV-2 infections [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%